Molecular hydrogen production from wastewater electrolysis cell with multi-junction BiOx/TiO2 anode and stainless steel cathode: Current and energy efficiency - Cho, Kangwoo; Hoffmann, Michael R. (ELSEVIER SCIENCE BV, 2017)
Electrochemical hydrogen evolution reaction (HER) has been recognized as a viable approach to generate a clean energy fuel. However, substantial technical breakthroughs are needed to reduce the costs for electricity and chemical reagents. In this study, we explore a specific wastewater electrolysis cell (WEC) as an alternative of decentralized H-2 production coupled with onsite water treatment. A prototypical WEC consists of a multi-junction semiconductor anode and a stainless steel cathode paired in single compartment cell. A distinct layer of BiOx/TiO2 on anode surface had relatively low crystallinity that was shown to be beneficial for higher oxide formation and O-2 evolution. The over-potential and Tafel slope of the BiOx/TiO2 anode were determined to be 0.32 V and 120 mV decade(-1). In a single compartment WEC with a NaCl electrolyte ([Cl-] <= 50 mM), the current density (j) ranged up to 500 A m(-2) at cell voltages less than 6V, while the current efficiency (CE) for free chlorine (FC) evolution showed maximum value near 0.3. The CE and energy efficiency (EE) for the HER were assessed using NaCI solutions (50 mM with or without 2.5 g L-1 urea) and real wastewater with variable compositions ([Cl-]: 6-33 mM, [chemical oxygen demand]: 60-790 mg L-1). The ohmic resistance of wastewater electrolyte rules out the usage of membrane separation, resulting in side reactions such as reduction of O-2 whose CE values monotonically decreased with an increasing j under the diffusion controlled regime. Chloride ions reduce the electron consumption during O-2 reduction, while elevated levels of FC significantly lower the CE for the HER. The combined presence of oxidizable organic compounds and Cl- enhance the CE for the HER as long as the concentration of organics is enough to quench FC to maintain a pseudo steady-state concentration. The highest CE (0.8) and EE (0.23) for HER were observed during electrolysis of real wastewater at j values exceeding 200 A m(-2). However, a dependency of value of EE on the applied cell voltage needs to be addressed further. (C) 2016 Published by Elsevier B.V.
Keywords: ELECTROCHEMICAL OXIDATION; HYPOCHLORITE PRODUCTION; OXYGEN REDUCTION; GAS EVOLUTION; ELECTRODES; CHLORINE; FUEL; ELECTROCATALYSTS; DEGRADATION; COATINGS